The salience of genomic information to reproductive autonomy: Australian healthcare professionals’ views on a changing prenatal testing landscape - Kerryn Drysdale; J. L. Scully; L. Kint; K.-J. Laginha; J. Hodgson; I. Holmes; K. L. MacKay; A. J. Newson (New Genetics and Society)
Genomic testing in prenatal care is rapidly advancing and it is now possible to obtain an entire fetal genome via a blood test administered in early pregnancy. In the pursuit of reproductive autonomy, more tests are being offered to more people, for an ever-increasing range of indications. Health professionals who provide pregnancy care are at the vanguard of prenatal testing, yet their views on the impact of technology advancements remain under-explored. Qualitative interviews with Australian healthcare professionals revealed that they value prenatal testing for its information-giving potential. However, the rationale underpinning testing reveals a tension between professionals’ desire for certainty and patients’ expectation that they will be reassured. Coupled with the greater salience of genomic information over other forms of knowledge in prenatal care, we suggest that the unchecked pursuit of information by way of genomic technologies in prenatal testing may paradoxically constrain reproductive autonomy in practice.